Odnajdywanie godności w konflikcie wychowawczym – piaskownica - Ruciński, Staniwsła (Horyzonty Wychowania, 2017)
Conflicts among children have deeper sources. The underlyingcause is complications whose recognition requires psychological,sociological and other tests. The children do not understand this themselves. Neither do the parents. They need specialist advice. But this help involves explaining the conflicts rather than understanding them and may bring about the ethical assessment of child’s behaviour, and encouraging the child to behave in a different way which is justified by this assessment, which might give rise to a new conflict among the children andthe educator who is controlling them.The story described illustrates that it would be better to show the children what they actually do attacking each other and face them with the question what victory means for them. And if the conflict appears ostensible, then victory is not necessary at all. What may emerge is a chance for a different look at the other person as somebody who we do not really want to harm, since he might be worth concern rather than painful caution as to what kind of person he should be, or how to act.